PROPTOSIS IN ACUTE MYELOID LEUKEMIA: AN UNDER RECOGNIZED PRESENTATION OF HEMATOLOGICAL MALIGNANCY - Tanzeela Farah; Sumaira Khalil; Tariq Ghafoor; Muhammad Tahir; Awais Arshad (Khyber Medical University Journal, 2021)
OBJECTIVE: To determine the frequency of proptosis and associations of proptosis with demographic, clinical and hematological characteristics with acute myeloid leukemia (AML) in children.